Guiding the nations through fair low-carbon economy cycles: A climate justice index proposal - Furlan, Marcelo [UNESP]; Mariano, Enzo [UNESP] (Elsevier, 2021)
Since the climate change context is increasingly the focus of decision-makers, indices capable of helping them in the transition to a low-carbon economy are considered necessary. Therefore, the objective of this work is to propose an index of climate justice that includes factors of human development and climate action. The index was developed using the Data Envelopment Analysis (DEA) technique and, in this study, assessed the climate justice of 198 nations. After the calculation, statistical analysis was used to compare the climate justice of the aforementioned countries, grouped by level of development and geographical location. The results obtained were: a) there is currently no nation that fully guarantees climate justice to its population; b) there is a difference in the performance of climate justice between the Annex I, Non-Annex I and Least Developed Countries (LDCs) groups; c) nations located in Africa, Latin America and the Caribbean, Asia and Eastern Europe are similar in terms of climate justice index performance. The main contribution of this paper is in the fact that the proposed index can help policy-makers and national governments to define climate and development policies, creating a synergy between such policies.
Keywords: Capability approach; Climate change; Climate justice; Data envelopment analysis; Human development; Low carbon economy